2013
DOI: 10.1080/10408398.2012.691573
|View full text |Cite
|
Sign up to set email alerts
|

An Updated Review of Meat Authenticity Methods and Applications

Abstract: Adulteration of foods is a serious economic problem concerning most foodstuffs, and in particular meat products. Since high-priced meat demand premium prices, producers of meat-based products might be tempted to blend these products with lower cost meat. Moreover, the labeled meat contents may not be met. Both types of adulteration are difficult to detect and lead to deterioration of product quality. For the consumer, it is of outmost importance to guarantee both authenticity and compliance with product labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 180 publications
0
24
0
Order By: Relevance
“…Further studies are needed to clarify how different finishing alternatives, in terms of diet composition and length of the finishing period [ 3 , 25 , 33 , 34 ], may affect the patterns identified here and how other chemical markers such as terpenes and carotenoids [ 35 ], as well as stable isotope ratios [ 14 , 36 ], may be used in discriminating finishing systems. On the other hand, the possible discrimination among meat from indicus or taurus cattle may be further enhanced by combining meat properties with the information provided by genetic markers that may enable breed assignment [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies are needed to clarify how different finishing alternatives, in terms of diet composition and length of the finishing period [ 3 , 25 , 33 , 34 ], may affect the patterns identified here and how other chemical markers such as terpenes and carotenoids [ 35 ], as well as stable isotope ratios [ 14 , 36 ], may be used in discriminating finishing systems. On the other hand, the possible discrimination among meat from indicus or taurus cattle may be further enhanced by combining meat properties with the information provided by genetic markers that may enable breed assignment [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the significance of overall mean differences between quality traits of meats originating from different genetic groups or finishing systems, the variability among individual meat samples from the same group tends to be large, which may hinder the ability to reliably distinguish meat samples according to their genetic origin or production system. However, such distinction is essential if certification programs are adopted and appropriately verified [ 14 ], and various tools such as physical characteristics, chemical markers, genetic polymorphisms, etc., have been proposed for sample verification and assignment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The method developed in this study showed sensitivity and specificity in the quantification of pork meat in commercial processed meat products. Nowadays, to strengthen the above-described analytical methods, multivariate statistical techniques (chemometrics) are used and appear effective to determine meat authenticity as reviewed by Vlachos et al (2016). Chemometrics techniques (PCA, LDA, SIMCA, PLS-DA and PLS) can provide simple, rapid and low-cost methods for meat analysis, including the possibility of nondestructive measurements.…”
Section: Analytical Strategies To Assess Meat Authenticity: Methods Amentioning
confidence: 99%
“…DNA-based technique with polymerase chain reaction [38,44] is a common technique in food authentication testing to ensure halal and kosher brand food products adhere to the standards. However, most of these techniques still require substantial sample preparation or some have very high sensitivity to adulterants and prone to give undefined results if all procedures are not followed exactly.…”
Section: Food Authentication Detectionmentioning
confidence: 99%